Dual-mode topological rainbow based on Kagome sandwich structure - Zhang, Hongxiang (2025)
Topological slow light offers an attractive platform for enhancing light-matter interaction because of its immunity to backscattering and robustness to defects. Most topological rainbow trapping structures are designed to support only one mode during frequency routing. However, in this work, we have designed a dual-mode topological rainbow trapping structure to enrich the functionality of frequency routing in slow light, based on Kagome sandwich structure. With the expanding perturbation index m decreasing gradually, the proposed structure supports coupled topological dual-mode edge states. Through the theoretical and numerical calculations, the group velocity of dual-mode edge states can be slowed to near-zero areas, resulting in the trapping of light at the corresponding positions. Our work introduces a new approach to utilizing coupled topological edge states for building multifunctional slow light optical devices.